Ductility limit diagrams for superplasticity and forging of high temperature polycrystalline materials. (1st August 2020) - Zhang, Wei; Gao, Yanfei; Feng, Zhili; Wang, Xin; Zhang, Siyu; Huang, Lan; Huang, Zaiwang; Jiang, Liang
Abstract: A mechanistic understanding of the ductility limit diagrams is of critical importance, but it still remains elusive for a multitude of high temperature materials processing techniques, such as superplastic forming and hot forging. The relevant failure modes for the former are necking at high strain rates and intergranular cavitation at low strain rates, while those for the latter include the competition between longitudinal fracture and shear band. The comparison between the Arrhenius processes for grain boundary diffusion and grain interior creep defines a length scale that dictates whether the grain boundary cavity growth is diffusive or creep-constrained. A quantitative assessment of these damage evolution processes leads to the delineation of the dominant parametric spaces for individual failure modes, and thus superplasticity and forging limit diagrams are derived and compared to available experiments in literature. Graphical abstract: Ductility limits in high temperature processing of polycrystalline materials are analyzed from a quantitative assessment of intergranular cavity failure, as competing with necking and shear-band failure modes. The commonly believed practice of using high temperature and low strain rate to prevent high-temperature failure works for necking and shear band, but not for intergranular cavity failure. Excellent agreement with prior experiments which have not been mechanistically explained. Image, graphical abstract